TERRITORIALIDADES DO OESTE DE SÃO PAULO: transformações e interpretações - Losnak, Célio José (Universidade Estadual Paulista Julio de Mesquita Filho, 2017)
ABSTRACT This paper reflects on the territorial formation of the new west of São Paulo at the end of XIX century and beginning of XX century, seeking to identify some dominant structures such as the process of the town creation, building of railway networks and organization of the settlements. These structures were interpreted by historical agents, during various periods in the past, by means of dominant social representations of the territory, attributed to naturalized meaning and immanent to the region and defining of crucial agents for its constitution.

RESUMO Este artigo propõe uma reflexão em torno da formação territorial do novo oeste de São Paulo no final do século XIX e início do século XX, buscando identificar algumas estruturas dominantes, tais como os processos de criação de cidades, de instalação de redes ferroviárias e organização da ocupação. Essas estruturas foram interpretadas pelos atores históricos, em diversos momentos do passado, por meio de representações sociais dominantes do território, atribuidoras de sentido naturalizado e imanente à região e definidora dos agentes decisivos para a sua constituição.
Territorialities of The São Paulo West: transformations and interpretations
Keywords: São Paulo; Territory, West, City, Railway; São Paulo; Território; Oeste; Cidade; Ferrovia.